INTERACTIVE METHODS OF STUDYING THE RUSSIAN LANGUAGE AS A MEANS OF FORMING LANGUAGE COMPETENCE OF NON-LINGUISTIC UNIVERSITY STUDENTS - Atamukhamedova Gozal Sabirdjanovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article attempts to analyze the use of advanced forms and methods that are used by teachers of foreign languages in relation to the formation of students’ speech competencies in the educational process. The features and specifics of the use of interactive methods of teaching a foreign language in higher educational institutions are considered. The expediency of using interactive methods is considered, which allow making classes more diverse, enabling students to demonstrate speech independence, to realize communication skills and speech skills. The expediency of using interactive methods focused on the activation of students’ creative thinking is proved.